TI_GERICHTE 12.2018.16 vom 17. Juli 2019 , Compravendita immobiliare - pagamento di un terzo - lite priva d'oggetto? - TI Tribunale d'appello (2019)
Compravendita immobiliare - pagamento di un terzo - lite priva d'oggetto?